The Hen or the Egg: Inflammatory Aspects of Murine MPN Models - Jonas S. Jutzi; Heike L. Pahl (Mediators of Inflammation)
It has been known for some time that solid tumors, especially gastrointestinal tumors, can arise on the basis of chronic inflammation. However, the role of inflammation in the genesis of hematological malignancies has not been extensively studied. Recent evidence clearly shows that changes in the bone marrow niche can suffice to induce myeloid diseases. Nonetheless, while it has been demonstrated that myeloproliferative neoplasms (MPN) are associated with a proinflammatory state, it is not clear whether inflammatory processes contribute to the induction or maintenance of MPN. More provocatively stated: which comes first, the hen or the egg, inflammation or MPN? In other words, can chronic inflammation itself trigger an MPN? In this review, we will describe the evidence supporting a role for inflammation in initiating and promoting MPN development. Furthermore, we will compare and contrast the data obtained in gastrointestinal tumors with observations in MPN patients and models, pointing out the opportunities provided by novel murine MPN models to address fundamental questions regarding the role of inflammatory stimuli in the molecular pathogenesis of MPN.